Crystallite size induced crossover from paramagnetism to superparamagnetism in zinc ferrite nanoparticles - Singh, Jitendra Pal; Gautam, Sanjeev; Srivastava, R. C.; Asokan, K.; Kanjilal, D.; Chae, Keun Hwa (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2015)
Present work investigates the crossover from paramagnetism to superparamagnetism as a function of crystallite size in zinc ferrite nanoparticles using near edge X-ray absorption spectroscopy. Synthesized paramagnetic and superparamagnetic nanoparticles exhibit presence of Fe2+ and Fe3+ ions with dominant concentration of Fe3+ ions. Fe L- and O K-edges spectra of paramagnetic nanoparticles consist of more intense spectral features compared to that of superparamagnetic nanoparticles. This reflects enhanced t(2g) and e(g) symmetry states of Fe-O hybridized states in paramagnetic nanoparticles induced by increased degree of crystallization. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: X-RAY-ABSORPTION; OXYGEN K-EDGE; CATION DISTRIBUTION; MAGNETIC-PROPERTIES; DIELECTRIC-PROPERTIES; NEUTRON-DIFFRACTION; SPINEL-GRAPHENE; TEMPERATURE; MOSSBAUER; ZNFE2O4